Transmisión en HVDC para generación eólica (2020)
Wind generation systems have taken on great importance, because these systems produce cleaner energy and are a strong alternative to replace thermal generation plants. These systems have different configurations and ratings, whether they are rated by shaft arrangement or rated by speed. One of the great drawbacks that these generation systems could have is the reliability when generating power, this problem occurs because the wind speed is not constant, this causes that, at different moments of time, it has less or greater availability of energy. A strong solution is to implement an HVDC transmission system, which has great advantages when it comes to transporting energy. Transmission in HVDC is possible thanks to electronic power converters, which have a rectification stage and an inversion stage. By means of these devices, it is possible to control the flow of active and reactive power that is injected into the grid, having control of the flow of power, a fixed amount of energy can be provided, solving the reliability problem that wind turbines presented. In this document, the DigSILENT PowerFactory program is used to model an HVDC transmission system, the contribution of these systems to the electrical network is observed and how the power flow that these systems inject into the network can be controlled.